IDENTIFIKASI EKSTRAK DAUN KOPASANDA (Chromolaena odorata Linn) TERHADAP SEL ANTIPROLIFERASI TIKUS LEUKEMIA L1210 - Muhammad Fitrah (Jurnal Farmasi UIN Alauddin Makassar, 2016)
The anticancer activity of the extract kopasanda leaf against leukemia cells L1210. Simplicial kopasanda leaves extracted by maceration terraced with solvent n-heksan, etil asetat, etanol, and water. Test antiproliferative activity against leukemia cells L1210 to the extract in an instant four vitro indicate that IC50 extract respectively 9,2982 μg/mL (etil asetat), 11,3397 μg/mL air, 13,6176 μg/mL (etanol), and 14,1645 μg/mL (n-heksan).